Pengaruh Cash Holding, Nilai Perusahaan Dan Leverage Terhadap Income Smoothing Pada Perusahaan Manufaktur Sub Sektor Plastik Dan Kemasan Di Bursa Efek Indonesia (Bei) Tahun 2014-2018 - Muhammadharris Suwandi; Fauzi Arif Lubis; Nurwani (Ali Institute of Research and Publication, 2022)
Abstract The purpose of this research was to examine the influence of cash holding, firm value, and leverage on income smoothing partially and simultaneously. The population of this research was 15 hotel, restaurant, and tourism companies listed in the Indonesia Stock Exchange in the period of 2014-2018 and samples of 6 companies by using purposive sampling technique. The data were processed by using multiple linear regression analysis. The result of the research showed that first, working capital had influence positive and significant on profitability. Secondly showed that liquidity had influence positive and significant on profitability. Thirdly showed that working capital and liquidity influence significant on profitability simultaneously.